Do Progressive Sensorimotor Training Devices Produce A Graded Increase in Centre of Mass Displacement During Unipedal Balance Exercises in Athletes - Nina Gras; Torsten Brauner; Scott Wearing; Thomas Horstmann (Applied Sciences, 2020)
Progression of the difficulty of agility exercises in sport is often achieved by changing the stability of the support surface via graded sensorimotor training devices. However, little is known about the challenge imposed to postural equilibrium by these graded devices. This study quantified the instability provided by four sensorimotor training devices typically used to enhance athletic performance; three progressively unstable balance pads (ST1–3) and an oscillatory platform (PM). Twenty-five (13 female, 12 male) young adults (age, 26 ± 3 yr; height, 1.76 ± 0.10 m; and weight, 69 ± 12 kg), completed seven unipedal balance conditions involving stable and progressively unstable surfaces that involved four sensorimotor training devices (ST1-3, PM) and their combination (PM-ST1, PM-ST2). An inertial sensor, mounted over the lumbar spine, was used to monitor Centre of Mass (COM) displacement in each condition. Potential differences in COM displacement between conditions were assessed using a mixed-model analysis of variance. COM displacement differed between training devices; with a progressive, though non-linear, increase in COM displacement from the most (ST1) to the least (ST3) stable balance pad. However, there was no significant difference in COM displacement between the least stable balance pad (ST3) and the oscillatory platform used in isolation (PM) or in combination with balance pads (PM-ST1, PM-ST2). These novel findings have important practical implications for the design of progressive sensorimotor training programs in sport.